REGRESI KUADRAT TERKECIL PARSIAL MULTI RESPON UNTUK STATISTICAL DOWNSCALING (Multi Response Partial Least Square for Statistical Downscaling) - Aji Hamim Wigena (FORUM STATISTIKA DAN KOMPUTASI, 2011)
In climatology partial least square regression (PLSR) can be used as an alternative technique in statistical downscaling based on global circulation model (GCM) output. PLSR is the technique to forecast not only one response but also multi responses to accommodate the correlation among responses. PLSR is compared to PCR (Principal Component Regression). The results show that PLSR is better than PCR and can be used to forecast rainfall simultaneously in more than one rainfall stations relatively as well as in one station. Keywords: statistical downscaling, PLSR, PCR, multi responses